Long-Term Cognitive Decline After Newly Diagnosed Heart Failure: Longitudinal Analysis in the Cardiovascular Health Study - Hammond, Christa A. (Circ Heart Fail, 2018)
BACKGROUND. Heart failure (HF) is associated with cognitive impairment. However, we know little about the time course of cognitive change after HF diagnosis, the importance of comorbid atrial fibrillation (AF), or the role of ejection fraction (EF). We sought to determine associations of incident HF with rates of cognitive decline and whether these differed by AF status or reduced versus preserved EF. METHODS AND RESULTS. Participants were 4,864 men and women aged ≥ 65 without a history of HF and free of clinical stroke in the Cardiovascular Health Study, a community-based prospective cohort study in the United States, with cognition assessed annually from 1989/90 through 1998/99. We identified 496 participants with incident HF by review of hospital discharge summaries and Medicare claims data, with adjudication according to standard criteria. Global cognitive ability was measured by the Modified Mini-Mental State Examination (3MSE). In adjusted models, 5-year decline in model-predicted mean 3MSE score was 10.2 points (95% CI: 8.6, 11.8) after incident HF diagnosed at age 80, compared with mean 5-year decline of 5.8 points (95% CI: 5.3, 6.2) from age 80 to 85 without HF. The association was stronger at older ages than at younger ages, did not vary significantly in the presence versus absence of AF (p = 0.084), and did not vary significantly by reduced versus preserved EF (p = 0.734). CONCLUSIONS. Decline in global cognitive ability tends to be faster after HF diagnosis than without HF. Clinical and public health implications of this finding warrant further attention.